3.1: Invited Paper: Electrowetting display: Towards full‐color video reflective display. (26th August 2021) - Guo, Yuanyuan; Tang, Biao; Yuan, Dong; Bai, Pengfei; Li, Hao; Yi, Zichuan; Deng, Yong; Zhou, Rui; Zhong, Benpeng; Jang, Hongwei; Henzen, Alex; Zhou, Guofu
Abstract : Current mainstream display technologies include liquid crystal displays (LCD), Organic Light‐Emitting Diode (OLED), and electrophoretic paper displays (EPD). The electrowetting display (EWD) is expected to become a new member of the display family due to its fast response speed, paper‐like reflective display. In recent years, technology breakthroughs of electrowetting have been made in EWD. EWD has achieved playing dynamic videos with the comparable performance of LCD and displays print‐level color images. The current EWD has reached the color gamut NTS 50%, refresh time 12ms, and 260000 colors display. The potential applications of EWD including education, mobile terminals, e‐book readers, outdoor billboards, etc. The advantage of EWD will create new markets which are not accessible now.